BC2F2 LOCAL RICE GENOTYPES FIELD TEST AT NON-TIDAL SWAMP IN SOUTH SUMATRA PROVINCE - Fitri, Milia; Hasmeda, Mery; Suwignyo, Rujito A. (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Non-tidal swamp is one of suboptimal land available to increase rice production in Indonesia. The problems is stagnant flooding during vegetative growth phase of the crop. Therefore, it is important to have rice varieties that tolerant flooding. Crossing and selection have been conducted to obtaine BC2F2 genotype from local swamp rice varieties, i.e. Siam, Pegagan and Pelita Rampak. This research was aimed at knowing the growth and production of several genotypes BC2F2 and their parental varieties, Siam, Pegagan and Pelita Rampak. The research was conducted in non-tidal swamp in Village Sako, sub-district Rambutan, District Banyuasin, South Sumatra from October 2017 to March 2018. Rice genotypes have been used BC2F2 Siam, BC2F2 Pegagan, and BC2F2 Pelita Rampak, and their parental varieties i.e. Siam, Pegagan, and Pelita Rampak. The results showed that genotype BC2F2 had vegetative and generative characters different from those of Siam, Pegagan, and Pelita Rampak. The production of the tested rice varieties was high, ranged from 4.52 to 7.95 tonnes per hectare. The best of each genotypes planted in the first season were SM 2, PGG 4, and PLR 3. While the best BC2F2 of each genotypes planted in the second season were SM 2, PGG 3, and PLR 3.